Weierstrass and Jacobi elliptic, bell and kink type, lumps, Ma and Kuznetsov breathers with rogue wave solutions to the dissipative nonlinear Schrödinger equation. (July 2022) - Seadawy, Aly R.; Rizvi, Syed T.R.; Ahmed, Sarfaraz
Abstract: This paper exposes Weierstrass elliptic, Jacobi elliptic, Bell type, kink type, bright soliton, periodic and some other soliton solutions for (1 + 1)-dimensional dissipative nonlinear Schrödinger equation (d-NSLE) by applying newly developed sub-ODE method. The d-NLSE is applied to model the dissipative self-modulating monochromatic waves with dispersion. The lump solutions, lump with one kink, lump periodic, interaction with kink, manifold periodic, Ma breather, Kuznetsov-Ma breather and rogue wave solutions for governing model are derived via symbolic computation with the appropriate transformation function technique. Highlights: The applications of Radhakrishnan-Kundu-Lakshmanan dynamical model. The optical multiwave solutions structures are obtained. The analytical modified methods are applied. Various rational solution with interactions Homoclinic breather, periodic cross-kink solutions with interactions.